Mechanism for Settlement of Land Tenure in the Context of Forest Area Planning (PPTPKH) in Karimun Regency - Dedy Sunarto; Darwis Anatami; Siti Nurkhotijah; Nicha Suwalla; Silvia Handayani (Melayunesia Law, 2025)
This study examines the mechanism for resolving land tenure issues within the framework of Forest Area Structuring (PPTPKH) in Karimun Regency. The central problem lies in the mismatch between community land tenure and the designation of forest areas, which often generates legal as well as social conflicts. This research employs a normative juridical method with statutory and conceptual approaches, complemented by empirical data through interviews and document analysis at the regional level. The findings indicate that the implementation of PPTPKH in Karimun Regency faces several challenges, including regulatory disharmony between central and local governments, limited spatial data, and weak institutional coordination. The resolution mechanism applied involves administrative and technical verification of land claims, assessment based on principles of social justice and legal certainty, and granting legal access through forest area release, land-swap schemes, or the allocation of land rights under agrarian law. However, the implementation remains suboptimal due to overlapping authorities and limited institutional capacity. This study recommends regulatory harmonization, strengthening land and forestry databases, and enhancing the role of local governments in the PPTPKH process to achieve a fairer, more transparent, and sustainable resolution of land tenure issues.